PENERAPAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Mutiarani Mutiarani; Zunia Miranda; Dinna Cilvia Asri; Bobbi Rahman (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2015)
TIMSS 2011 and PISA 2012 results for mathematical communication skills of junior high school are considered low. One of eforts to increase their mathematical communication skills are using of problem solving method. Problem solving method gived opportunity for student to express of mathematic idea in coherent to their teacher or another students, so they can practice their mathematical communication skill. This case is the background for reasearcher to do some research in mathematical communication skill using problem solvig method. The purpose of this research is to increased mathematical communication skill of students. Type of this research is quasi experiment with nonequivalen control group design which is compare of control class with experiment class. Population for this reasearch are students second grade in junior high school 2 Pagedangan. Samples for this reasearch is students in VIII 5 class with 31 students as control class and students in VIII 6 class with 30 students as experiment class. In control class, learning activity using conventional method while in experiment class using problem solving method. Data in this research are collected with giving pretest question and posttest question as analysis question. Testing of hypotheses using with normality test and mann-whitney test. Result from this research are increased mathematical communication skill for students in experiment class which is used problem solving method are better tahn increased mathematical communication skill for students in control class which is used conventional method. Another result is positive attitude of students to mathematic learning used problem solving method.